Gambaran Personal Higiene Dan Keadaan Sanitasi Industri Tempe UD Andika Panguripan Di Desa Tagtag Kaja Kecamatan Denpasar Utara Tahun 2019 - Ni Luh Putu Ayu Swandewi; Ni Ketut Rusminingsih; Nyoman Purna (Poltekkes Kemenkes Denpasar, 2019)
Abstract.AndikaPanguripan trading business is a home industry that produces tempe. AndikaPanguripan's trading business is in TagtagKaja Village, Singasari Utara street, Uma Punggul II alley No. 31, which was established in 2010, has 10 employees.The purpose of the study was to determine the description of personal hygiene and the sanitation conditions of AndikaPanguripan Trade Business tempe in TagtagKaja Village, North Denpasar Subdistrict in 2019. The research method used is descriptive research method with cross sectional approach.Data collection is done by observation and interview.Examination is carried out with observation sheets on the state of sanitation (buildings and sanitation facilities, food sanitation) and personal hygiene.The collected data is processed and presented in the form of tables. The results of this study are that the condition of buildings and sanitation facilities is categorized as moderate with 9 (43%), food sanitation is categorized as being moderate with a score of 13 (62%), sanitation conditions are categorized as being moderate with a score of 22 (52%) and personal hygiene of employees categorized as being moderate with a score of 6 (60%).Conclusions from the results of research on the state of sanitation, food, building and personal hygiene AndikaPanguripan trading business is included in the medium category.Suggestion is to make repairs to buildings and sanitation facilities at tempe processing sites, maintain cleanliness of tempe processing facilities, and employees to apply personal hygiene while working. Keywords: personal hygiene and sanitation